Pertanggungjawaban Notaris yang Dinyatakan Pailit Terhadap Akta yang Dibuatnya - Wenty Valda Estrada Pakpahan; Gde Made Swardhana (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of writing research is to find out the position of a Notary's deed after experiencing bankruptcy and the responsibility of a Notary who is declared bankrupt regarding the deed they make. This research was analyzed using normative research methods. The approach used is statutory and conceptual. The results of the research obtained are: 1. The position of the deed that was made by the Notary before going bankrupt and in accordance with the procedures stipulated by statutory regulations, then the deed that was made still has perfect evidentiary power, however the notary protocols that have been declared bankrupt is transferred to the Notary receiving the protocol established by the MPD. Meanwhile, if a notarial deed is made after the notary has been declared bankrupt by a court decision, the notary no longer has the authority to make the deed, and the deed made becomes a private deed. 2. Based on the theory of responsibility by Hans Kelsen, the theory of responsibility that can be used in relation to Notaries who are declared bankrupt is the theory of absolute responsibility. In this case, the Notary does not anticipate that he will experience bankruptcy which will cause his assets to be confiscated and he will be dismissed from his position as Notary. Thus, a Notary who is dismissed from his position due to bankruptcy can still be held civilly or criminally liable for the deed he has made even though the notarial protocol has been submitted to the Notary Receiving the Protocol.